Perbedaan Profil Bakteri pada Lendir dari Vagina antara Persalinan Preterm dan Persalinan Aterm di Ruang Bersalin Badan Rumah Sakit Umum Prof. Dr. Soekandar Mojosari Mojokerto - Saudah, Noer (JURNAL KEPERAWATAN BINA SEHAT, 2010)
Preterm delivery is one of the factors that lead to the increasing infant mortality rate in Indonesia. However, the cause of preterm delivery remains unclear. Most of the cases (70%) are predominated by spontaneous delivery. The pathophysiology of preterm delivery is a concept that remains being studied and investigated intensively. Preterm delivery is an obstetric problem, which, until recently, has no effective prevention and treatment due to unclear causes. It is therefore important to find the causes of the problem in order to prevent and to reduce its incidence.This study was conducted in Delivery Wards, Prof Dr Soekandar Hospital, Mojosari, Mojokerto, and samples were delivered to the laboratory at the Department of Medical Microbiology, Airlangga University, Faculty of Medicine. This study lasted between March to July 2008. The independent variable was bacterial type in vaginal mucosa, while the dependent variable was the preterm delivery. This study used observational design. Samples were recruited using consecutive sampling, totally 36 samples, which comprised of 18 preterm deliveries and 18 aterm deliveries. Preparation was made on object glass for staining and samples kept in transport media amies were bred to identify the type of growing bacteria. Data were analyzed using Chi-square test to compare the type of bacteria in vaginal mucosa from preterm and aterm delivery with significance level of 95% (p < 0.05).The result revealed significant difference in bacterial type of Streptococcus b hemolyticus and Streptococcus pyogenes with significance level of 0.041.In conclusion, there is a difference of bacterial profile from vaginal mucosa in preterm and aterm delivery. Bacterial type identification as the cause of genital infection in pregnant women with the symptom of discharge should be undertaken as the reason for treatment to prevent aterm delivery.Keywords: bacterial type, preterm delivery, aterm delivery